PERILAKU KESEHATAN MASYARAKAT PESISIR DESA MORODEMAK KECAMATAN BONANG KABUPATEN DEMAK - Khoirin Nida; Ani Margawati; Af’idatul Latifah (Endogami: Jurnal Ilmiah Kajian Antropologi, 2022)
Each community has different health behaviors that have been adapted to their respective cultures. Health perceptions and behaviors carried out by the people of Morodemak have a major influence from the unstable living environment. The people of Morodemak often ignore health problems that occur because they are considered to have other problems that are considered more important. The purpose of this research is to describe and find out health behavior is carried out by the coastal society of Morodemak. The theory used in this research is the theory of Preced Proceed by Lawrence Green and health behavior according to Notoatmodjo. This research is qualitative research with an emic perspective, data collection techniques carried out by participant observation and in-depth interviews method. The results of this research indicate that the perception of the coastal society of Morodemak on health has an influence on their health behavior. People who live in Morodemak have their own assessment of their health condition so that health behavior whose carried out by the coastal society of Morodemak is based more on what they believe and only on what they need.